Foundations of Curriculum Development and Management - Bauzon, Prisciliano T. (Mandaluyong City, 2001)
This book provides a comprehensive overview of the principles and practices involved in curriculum development and management within the Philippine educational context.
Keywords: Curriculum planning; Education - Curricula